Differences in Specific Mass Density Between Dinoflagellate Life Stages and Relevance to Accumulation by Hydrodynamic Processes. Issue 5 (17th June 2021) - Persson, Agneta; Smith, Barry C.; Alix, Jennifer H.; Li, Yaqin; Holohan, Bridget A.; Wikfors, Gary H.
Abstract : One previously unstudied aspect of differences between sexual and asexual life stages in large‐scale transport and accumulation is density (mass per unit volume) of cells in each life stage. The specific density was determined for Scrippsiella lachrymosa cells in medium with and without nitrogen (N) enrichment through density‐gradient centrifugation. Growth medium without N addition is often called "encystment medium" when used for the purpose of resting cyst formation in cyst‐forming dinoflagellates; mating gametes are usually seen after 2–3 days. Significant differences in specific density were found after 2 days in encystment medium simultaneously with the observation of typical gamete swimming behavior and mating. The specific density of cells in encystment medium was 1.06 g · cm −3 ; whereas, the specific density of cells in growth medium was 1.11 g · cm −3 . Cells in encystment medium were found to have significantly increased lipid content, reduced chlorophyll content, and reduced internal complexity. The findings may explain differential transport of less dense and chemotactically aggregating gametes into surface blooms in contrast to denser vegetative cells that perform daily vertical migration and do not aggregate. Passive accumulation of non‐migrating gametes into layers in stagnant water also can be explained, as well as sinking of zygotes when the storage of highly dense starch increases. Resting cysts had a density of over 1.14 g · cm −3 and would sink to become part of the silt fraction of the sediment. We suggest that differences in behavior and buoyancy between sexual and asexual life stages cause differences in cell accumulation, and therefore large‐scale, environmental transport could be directly dependent upon life‐cycle transitions.